LOCAL COLOR AND AMERICAN SLAVERY IN THE ADVENTURES OF HUCKLEBERRY FINN - Alya Nurhalimah; Nabila Githa Fasya; Nurholis; Windy Novia Ramadhanti (Cahaya Ilmu Bangsa Institute, 2025)
This paper discusses the use of local color and American slavery in Mark Twin's ‘The Adventure of Huckleberry Finn’. The novel uses local color to create a real picture of life in the American South in the 19th century, through the use of local dialects, descriptions of scenery and environments, and local community habits. Huck Finn, as the main character in the novel, is young and innocent, and he does not enslave black people, which in 19th century South America still existed. His friendship with Jim, a slave trying to escape from being caught by slave hunters, is central to the story and social issues. Jim is not only Huck's friend and protector, but also a character who represents the injustice experienced by slaves. By combining the discussion of local color and American slavery, we as readers discover and reflect on the social and moral values of the time.